Effectiveness of Modified ZnAl-LDH Developed with POM for Competitive Adsorption of Heavy Metals in Purification Systems - Normah, Normah; Oktriyanti, Melantina; Badri, Arini Fousty (Indonesian Journal of Material Research, 2024)
This study investigates the effectiveness of ZnAl-LDH modified with polyoxometalate (POM) as an adsorbent material in the competitive adsorption of heavy metal ions Cr(VI) and Fe(II). The material was synthesized using the co-precipitation method, resulting in ZnAl-LDH@POM with enhanced interlayer spacing, a specific surface area 14 times more significant, and increased surface-active sites. Characterization using XRD, FT-IR, and BET confirmed the successful structural modification and improved adsorption properties. Kinetic studies revealed that adsorption followed a pseudo-second order kinetic model, achieving maximum efficiency within 50 minutes. Isothermal analysis demonstrated maximum adsorption capacities (???????????????? ) of 92.95 mg/g for Fe(II) and 44.44 mg/g for Cr(VI). These findings highlight the potential of ZnAl-LDH@POM as an effective adsorbent for treating heavy metal-contaminated wastewater.